Pengembangan Sumber Daya Manusia terhadap Peningkatan Kompetensi Dikantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean B Medan - Fadilatul Ummah; Mudji Kuswinarno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research examines the influence of human resource development on the competency and performance of employees at the Customs and Excise Supervision and Service Office Type Madya Customs B Medan. Through interviews with five employees of the Medan Customs and Excise Supervision and Service Office of Type A Customs, this research identified the steps taken by the leadership to improve employee competency and performance, as well as overcome the obstacles faced. The main focus of research is development programs which include training, skills and mental development, assessment, and providing motivation through capacity building activities. The theory used refers to the concept of employee performance according to Sedarmayanti, with a qualitative approach that includes observation, interviews and collecting supporting documents. The research results show that the human resource development carried out plays an important role in improving the competency and performance of employees in the office.